Channa striatus cream down-regulates tumour necrosis factor (TNF)-alpha gene expression and alleviates chronic-like dermatitis in mouse model - Mohamad Isa, Irma Izani (Elsevier Ireland, 2016)
Ethnopharmacological relevance: Haruan, Channa striatus, is a freshwater fish which has been well-known locally to accelerate wound healing during post-operative and post-partum periods. The fish extract also has potent anti-inflammatory and analgesic properties.